REVIEW JURNAL: POTENSI DAUN NIPAH DALAM OBAT TRADISIONAL SEBAGAI AKTIVITAS ANTIINFLAMASI - Angellina Putri Petrisia; Chairul Saleh; Djihan Ryn Pratiwi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Nipah (Nypa fruticans Wurmb) is a mangrove plant from the Palmae tribe that grows along rivers that are affected by tides. The abundance of nipa palm in mangrove forests is quite high, so it has great potential to be developed. This review aims to discuss the potential anti-inflammatory activity of nipah leaves as traditional medicine, so that they can add value to nipah leaves and can be useful in the health sector. The literature search was carried out through Google Scholar and Scholar research papers related to the ability of anti-inflammatory activity in nipah leaves and other Arecaceae families. Nipah leaf extract contains secondary metabolites, namely flavonoids, phenolics, tannins, steroid saponins and triterpenoids. Flavonoids can function as inhibitors of cyclooxygenase and lipoxygenase enzymes so that they can be used to treat anti-inflammatory. Based on the literature, it can be concluded that nipah leaves are potentially effective as traditional medicine in treating inflammation or inflammation. Keywords: Nipah (Nypa fruticans Wurmb), anti-inflammatory and flavonoids